A Translation Studies Perspective to the Stage Adaptations of the Novel Beş Sevim Apartmanı by Mine Söğüt - Sağlam, Naciye (Istanbul University Press, 2022)
Mine Söğüt is known for her debut novel, Beş Sevim Apartmanı, a work in which the author’s experimental technique on the theme of belief adds a literary value to the expression of psychological issues. The novel was adapted to the stage by two different playwrites, and performed by two theater groups accordingly. This study aims to establish a perspective on the stage adaptations of Beş Sevim Apartmanı from the standpoint of Translation Studies and to evaluate these adaptations as intersemiotic translation. These two different stage adaptations reveal how linguistic signs can be translated into multimodal forms on stage. Additionally, revealing the overlapping and diverging features of the two adaptations is another outcome of the study. © 2022, Istanbul University Press. All rights reserved.
Mine Söğüt’ün Beş Sevim Apartmanı Romanının Tiyatro Uyarlamalarına Çeviribilim Perspektifinden Bakış
Keywords: adaptation; Beş Sevim Apartmanı; intersemiotic translation; Mine Söğüt; multimodality